Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1203/00006450-200202000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Ceramide Content and Lack of Apoptosis in the Chronically Hypoxic Neonatal Rat Heart

Abstract: To assess the effect of chronic hypoxia on cardiomyocyte apoptosis, we used an animal model that mimics cyanotic heart disease. Rats were placed in a hypoxic environment at birth, and oxygen levels were maintained at 10% in an air-tight Plexiglas chamber. Controls remained in room air. Animals were killed, and the hearts were harvested at 1 and 4 wk. Significant polycythemia developed in the hypoxic rats at 1 and 4 wk. Right ventricular mass in the hypoxic rats was 192% and 278% that of controls, and hypoxic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…The animal model used in this study is well described for studies of chronic hypoxia and results in a similar degree of hypoxia present in human infants with CHD [8,26,32]. The body weight of the chronic hypoxia rats was decreased, as has been demonstrated in all studies that have used a similar model [8,12,26].…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The animal model used in this study is well described for studies of chronic hypoxia and results in a similar degree of hypoxia present in human infants with CHD [8,26,32]. The body weight of the chronic hypoxia rats was decreased, as has been demonstrated in all studies that have used a similar model [8,12,26].…”
Section: Discussionmentioning
confidence: 63%
“…The body weight of the chronic hypoxia rats was decreased, as has been demonstrated in all studies that have used a similar model [8,12,26]. While the associated malnutrition may have played a role in the neurochemical alterations, the effects are likely to be minor.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…As previously described, an animal model mimicking cyanotic heart disease was studied [23,24]. Animal cages were placed in temperature-controlled rooms (22°C) with constant 12-hour light/dark cycle.…”
Section: Study Design and Methodsmentioning
confidence: 99%
“…Many studies were conducted to determine the effects of hypoxia or hyperoxia on ceramide. First, it was shown that upon exposure to chronic hypoxia, the myocardial mass was increased in a rat and mouse models of cyanotic congenital heart disease due to compensatory cardiac proliferation in the right ventricle (RV) [28,29]. This phenotype was associated with the absence of apoptosis, the relative decrease in total ceramide, specifically N-palmitoyl-D-erythro-sphingosine (C16-Cer) levels [30], and the significant increase of the precursor dihydro-N-palmitoyl-D-erythro-sphinganine (DHC16) in the RV.…”
Section: Ceramide and Cellular Signalingmentioning
confidence: 99%